Recent advances of hexaazatriphenylene (HAT) derivatives: Their applications in self-assembly and porous organic materials. Issue 7 (14th February 2018) - Yan, Xiao-Yang; Lin, Meng-Di; Zheng, Si-Tai; Zhan, Tian-Guang; Zhang, Xiang; Zhang, Kang-Da; Zhao, Xin
Graphical abstract: Highlights: The synthetic methods of hexaazatriphenylene (HAT) derivatives have been introduced. Some recent advances of HAT structure in the applications of supramolecular self-assembly have been highlighted. The recent developments of HAT-based porous organic polymers have been summarized. Abstract: As a rigid and planar aza-based heteroaromatic scaffold, hexaazatriphenylene (HAT) exhibits excellent electron-deficient property and high π-π stacking tendency, which makes it an ideal building block in the construction of supramolecular architectures and functional materials. In addition, HATs have also been picked out as building blocks for the construction of novel porous organic polymers, one of the most attractive fields of porous materials in the past decade, which includes intrinsic microporosity (PIMs), π-conjugated microporous polymers (CMPs), and covalent organic frameworks (COFs). In this digest paper, the synthetic methods of HAT derivatives have been briefly introduced and some recent advances of HATs in the applications of supramolecular self-assembly and porous organic materials have been highlighted.